Burnout Levels and Care Behaviours in Intensive Care Nurses: A Cross-Sectional, Multicentre Study - Efil, Sevda; TÜREN, SEVDA; Ayvaz, Meryem Yıldız; Bülbül, Elif; Yeni, Tuğba (Elsevier Sci Ltd., 2022)
Objective: To examine the relation between burnout levels and caring behaviours in intensive care nurses in Turkey, and the affecting factors. Research methodology/design: The research was conducted as a descriptive, cross-sectional and multi-centred study. Setting: In this study, an online questionnaire was applied in April and May 2021, using Google Form. A total of 460 intensive vare nurses responded to the questionnaire. Main outcome measures: Burnout was assessed with the Maslach Burnout Inventory, and care behaviours with the Caring Behaviours Inventory-24. Results: The nurses reported a high level of emotional exhaustion (73.9%) and depersonalization (52.2%), and a medium level of personal accomplishment (40%). The nurses' levels of perception of care quality were high (5.4 +/- 0.6). It was found that their highest score on the subdimensions was on knowledge and skills (5.6 +/- 0.5), and the lowest was on connectedness (5.2 +/- 0.7). There was a very weak, respectively weak correlation, between nurses' emotional exhaustion (r = -0.1), respectively depersonalization (r = -0.2), and poor care behaviours. There was a strong correlation between low personal accomplishment scores and poor care behaviours (r = 0.8). It was found that the mean scores of the nurses' exhaustion and care behaviours varied according to many descriptive characteristics, such as education, age, professional experience, the unit where they worked, communication difficulties, living conditions and whether they had chosen nursing willingly. Conclusions: It appears that the level of personal accomplishment, is the only subscale reflecting risk of burnout, that strongly correlates with care behaviour.
Keywords: Nursing; Critical Care; Nursing Care; Burnout; Caring Behaviour; Quality of Care